Efektivitas Penyusunan Rencana Kebutuhan Barang Milik Daerah di Badan Pengelola Keuangan Dan Aset Daerah Provinsi Sumatera Selatan - Sati, Yoranda Tiara; Syaparman, Syaparman; Iriani, Atrika (@-Publik: Jurnal Administrasi Publik, 2023)
The purpose of this study was to analyze the effectiveness of preparing regional property needs plans (RKBMD) at the Regional Financial and Asset Management Agency (BPKAD) of South Sumatra Province. The effectiveness of RKBMD preparation at BPKAD of South Sumatra Province is focused on the Effectiveness of RKBMD preparation at BPKAD of South Sumatra Province which includes: source approach, process approach, goals approach. This study uses a qualitative approach with a descriptive explanation level.. Data analysis techniques in this study were analyzed using an interactive model which includes three components of analysis, namely condensation, data presentation, drawing conclusions. The results of the study show that, based on the Resource Approach, the time for determining the RKBMD is often late from the predetermined schedule, due to the lack of human resources owned by the BPKAD of the South Sumatra Province, especially in the Secretarial Sector so that the preparation of the Provincial Government Property Needs Plan is still not optimal. The facilities owned by BPKAD of South Sumatra Province are quite adequate in carrying out government duties and functions, it's just that they are still lacking in terms of developing applications that can facilitate work and the unavailability of standard goods and standard needs, which is due to the application for preparing RKBMD not yet integrated with financial applications. Based on the Process Approach, the obstacles in preparing the RKBMD are partly due to the fact that the RKBMD is more technical in nature and better able to describe real spending. In the RKBMD, specifications for goods must be clear, and for the preparation of RKPBMD maintenance requirements, knowledge and technical skills regarding the condition of the goods are required. Therefore, for the preparation of RKBMD/RKPBMD users or parties related to the goods needed, such as: machine operators, technicians, technical officials, and others must be involved. Based on the Goals Approach, the Property User and/or the Proxy of the Property User proposes an RKBMD for the procurement of Provincial Government-Owned Goods guided by goods standards and requirements standards, then the RKBMD that has been determined is a requirement in the preparation and discussion of the Work Plan and PD Budget by the Government Budget Team Region of South Sumatra Province.